Bibliometric and bibliographical analysis on the use of crude oil treatment/recovery techniques from solid waste produced by the petroleum productiorn chain (Research, Society and Development, 2019)
As a result of the intense exploration and production activity, the petrochemical industry has been responsible for the generation of most solid waste produced in the world. Among these residues, oily sludge (BO) is in a prominent place, since it is produced in almost all stages of oil production and refining. Due to the high toxicity of these materials, improper disposal is considered a risk to the environment. Thus, the development of technologies capable of recovering the oil present in the sludge has been the object of several studies. In view of the above, this study aimed to investigate the scientific production related to the treatment/recovery of petroleum oily sludge through the use of pyrolysis, solvent extraction and microwave irradiation methods. Analysis of the results revealed that China is the country with the largest number of publications on treatment BO techniques. This may be related to the significant volume of BO generated annually in China, reaching 5 million tons in 2018. Although there is no pre-established industrial technology for BO treatment/recovery, published works point to pyrolysis as an efficient route, especially when associated with the use of catalysts (catalytic pyrolysis). The technique of microwave irradiation is also highlighted in the works as an ally of pyrolysis. With the joint use it was possible to obtain better results of BO oil recovery at lower temperatures. The solvent extraction technique had the advantage of working under mild temperature conditions (25 oC to 80 oC), using solvents such as n-hexane, cyclohexane, xylene, toluene, trichloromethane, methyl ethyl ketone, liquefied petroleum gas condensate and Na-AES. Although the technique is effective in removing oil from sludge, 100% of the solvent cannot be recovered at the end of the extraction process. This has been pointed as a disadvantage of this route. In general, it was observed that BO heterogeneity is one of the factors that hinder oil treatment/ recovery. The sector of the oil production chain from which the sludge is extracted, as well as its handling and conditioning are factors that may interfere with its treatment. Thus, the choice of one of the routes presented here, as well as the operating conditions to be used will be conditioned not only to the cost/benefit of the process but also to the intrinsic and storage characteristics of the sludge.